Análisis del turismo cultural y su impacto económico dentro de cantón Urdaneta, año 2021 - Yepez Troya, Kimberly Lisbeth (2022)
The present research work aims to analyze the potential of cultural tourism as one of the fundamental pillars for the development of the Urdaneta canton and how it would help to improve the economic development of the inhabitants who are dedicated to tourism within the sector, improving strategies and implementing new strategies for generating digital content to promote the tourist sites that exist within the canton, with a responsible look at the cultural care of the resources they possess. For the realization of this research work, a diagnosis of the tourism situation of the canton, the identification of the potentialities within the cultural tourism, and the economic importance it has within the local communities providing greater sources of employment, with alternatives to start new ventures focused on taking advantage of the tourist sites and customs that have the inhabitants of the different areas that make up Urdaneta, resulting in greater influx of domestic and international tourists and with this that the canton has national recognition as one of the tourist places that are characterized by having harmony with nature. A documentary research of the national and local situation of tourism and the affectations that this has generated in the economy of the families was carried out, in addition to a survey of 7 questions to the inhabitants of the canton Urdaneta, through these were used as a basis for the conclusions obtained where the potential places for tourism in the sector were identified, the identification of the importance of tourism for the development of commercial activities and improvements to be made for the development within the locality.